Retroperitoneal embryonal carcinoma/yolk sac tumor. A case report and a review of the histogenesis - Janda, J; Pecha, V; Petrík, F; Cízek, F; Berková, M; Stĕrba, J; Gottschalk, J (Archiv fur Geschwulstforschung, 1988)
A case of 26-year old man, with a large primary retroperitoneal tumor which showed the pattern of embryonal carcinoma as well as yolk sac tumor, is reported. The disease ran an aggressive course and led to death within 8 months from the onset of clinical symptoms. Characteristic histological and ultrastructural patterns with Schiller-Duval bodies and adenocarcinomatous differentiation were accompanied by diffuse expression of alpha-fetoprotein and human chorionic gonadotropin expression in isolated cells, as well. The histogenesis of the tumor may be interpreted in terms of the reflection of the very early stages of the embryonal development rather than by the totipotent-neoplastic-germ-cell approach.
Keywords: Retroperitoneal Neoplasms; Teratoma; mezonefrom; mužské pohlaví; dospělí; retroperitoneální nádory; teratom; Adult; Humans; Mesonephroma; lidé; Male